FGFR2 testing in cholangiocarcinoma: translating molecular studies into clinical practice - Angerilli, Valentina; Fornaro, Lorenzo; Pepe, Francesco; Rossi, Silvia Maria; Perrone*, Giuseppe; Malapelle*, Umberto; Fassan*, Matteo (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2023)
Cholangiocarcinoma (CCA) is a heterogeneous group of neoplasms burdened by a dismal prognosis. Several studies have investigated the genomic profile of CCA and identified numerous druggable genetic alterations, including FGFR2 fusions/rearrangements. Approximately 5-7% of CCAs and 10-20% of intrahepatic iCCAs harbor FGFR2 fusions. With the recent advent of FGFR-targeting therapies into clinical practice, a standardization of molecular testing for FGFR2 alterations in CCA will be necessary. In this review, we describe the technical aspects and challenges related to FGFR2 testing in routine practice, focusing on the comparison between Next-Generation Sequencing (NGS) and FISH assays, the best timing to perform the test, and on the role of liquid biopsy.